Analysis Of Nutrient Content And Organoleptic Test Of Fish Waste POC With The Addition Of Ecoenzyme - Papriani, Nada Pertiwi; Mishbach, Imam; Gea, Liyatin; Jannah, Miftahul; Yusriadi, Yusriadi; Ramadan, Rafsanjany (Jurnal Kimia Fullerene, 2025)
Nutrients in fish waste can cause pollution (eutrophication) when directly discharged into waters. Efforts to minimize this can be done by processing fish waste into POC. Making POC from fish waste can be done by adding ecoenzymes. The purpose of this study was to observe the organoleptic, pH and nutrient content of POC from fish waste with and without the addition of ecoenzymes. The stages of the study were ecoenzyme production, POC products, organileptic tests, pH observations, and analysis of nitrogen (N), phosphorus (P), and potassium (K) content. Based on the results of the study on the observation of organoleptic odor tests before fermentation, Bucket 1 without the addition of ecoenzyme has a slightly rotten and fishy odor, reddish brown in color, pH 6, after fermentation it has a sour and fishy odor, brown in color pH 5. Bucket 2 With the addition of ecoenzyme has a slightly rotten and fishy odor, reddish brown in color, pH 5, after fermentation it has a slightly sour and fishy odor, brown in color, pH 4. The NPK content in bucket 1 without the addition of ecoenzyme is 0.35%, 0.19%, 0.09%, in bucket 2 with the addition of ecoenzyme is 0.57%, 0.32%, 0.12%.